Management of Inter-relationship between Technology & Mental Health - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
In this modern world, full of technology, mental health is affecting the most. Various factors are there that are influencing the mental health such as stress, social media, personal life issues, tension about maintaining the social image, and many more similar factors are there that hamper the mental health of people these days. Some factors are controllable but some are really not. This research paper is all focused about to study and realize the management of inter relationship between mental health and use of technology along with its impact. In this research paper, a general counselling is done on youth and teenagers aging from (15-30 years) with the help of questionnaire and personal interview of individuals. This analysis helps in understanding the management done by different people. From future perspective, this study may help researchers to better understand about how to make balance between technology and mental health in life.